A Comparative Study on Commercial Aircraft Gliding Performance - Efendi, Naufal Wafifauzan; Jayadi, muhamad; Arifin, Mufti (FTK UNSURYA, 2025)
Aerodynamic principles are crucial for improving both efficiency and safety in commercial aircraft operations. This study compares three gliding strategies: (1) iterative calculation at a fixed 3° glide angle, (2) analysis of actual flight data from FlightRadar24, and (3) aerodynamic optimization using the drag polar method. The iterative approach produced relatively low descent rates 4.6–5.5 m/s and the longest glide times 1,100–1,323 s, offering safety benefits by enabling aircraft to reach more distant landing sites during emergencies. Actual flight data showed wider variations in descent rates 4.8–17.88 m/s and glide times 340–1,270 s due to operational requirements and ATC instructions. In contrast, aerodynamic optimization identified an ideal glide angle of 3.1°–4.1°, with higher descent rates 10.56–16.65 m/s but shorter glide times 366–577 s, representing the most efficient aerodynamic condition at maximum lift-to-drag ratio. Comparative analysis revealed that optimization median 512 s and actual data median 590 s yield greater aerodynamic efficiency, while the 3° fixed-angle approach median 1,186 s enhances safety margins. These results emphasize that glide strategy selection must balance efficiency and safety, integrating aerodynamic analysis with real operational data to support decision-making in commercial aviation